Relative age, talent identification and youth skill development: Do relatively younger athletes have superior technical skills? - Schorer, D.; Baker, J.; Büsch, D.; Wilhelm, A.; Pabst, J. (Talent Development & Excellence, 2009)
Relative age effects (RAEs) refer to differences among individuals in age-based cohorts typically used in sport. These effects usually favour relatively older members of the cohort and are thought to result from differences in maturation and experience among athletes of different chronological age. Recently, researchers suggested that relatively younger participants may not be as disadvantaged as previously thought. In two studies, we examined whether relatively younger athletes who were able to survive in a system that advantages their relatively older counterparts would develop superior technical skills. In study one, participants aged 13-15 years (n=140) drawn from a regional handball talent selection camp in Germany demonstrated a general relative age effect but no differences between relatively older and relatively younger athletes in physical body size (i.e., height/weight) or technical skills. In study two, similar tests were considered with a larger sample (n=478) and revealed similar results. Furthermore, there were no differences between those selected for the national youth team and those not selected. Differences in RAEs do not seem to be due to technical skills or body size variables. Moreover, the homogeneity of these results suggests causes of the relative age effect occur early in development.